Implementing protocols via declarative event patterns. - Walker, Robert J. (Software engineering notes.)
This paper introduces declarative event patterns (DEPs) as a means to implement protocols while improving their traceability, comprehensibility, and maintainability. DEPs are descriptions of sequences of events in the execution of a system that include the ability to recognize properly nested event structures. DEPs allow a developer to describe a protocol at a high-level, without the need to express extraneous details. A developer can indicate that specific actions be taken when a given pattern occurs. DEPs are automatically translated into the appropriate instrumentation and automaton for recognizing a given pattern. Support for DEPs has been implemented in a proof-of-concept extension to the AspectJ language that is based on advanced compiler technology. A case study is described that compares the use of DEPs in the implementation of a protocol (FTP user authentication) to the use of a set of other approaches, both object-oriented and aspect-oriented.